2017
DOI: 10.1111/tmi.12896
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset type 2 diabetes mellitus among patients receiving HIV care at Newlands Clinic, Harare, Zimbabwe: retrospective cohort analysis

Abstract: Objective To assess the incidence and associated factors of Type 2 Diabetes Mellitus (T2DM) among people living with HIV (PLHIV) in Zimbabwe. Methods We analyzed data of all HIV-infected patients older than 16 years who attended Newlands Clinic between March 1, 2004 and April 29, 2015. The clinic considers patients whose random blood sugar is higher than 11.1 mmol/L and which is confirmed by a fasting blood sugar higher than 7.0 mmol/L to have T2DM. T2DM is also diagnosed in symptomatic patients who have a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…In another study by Adrovandi et al, 2014, alcohol use was associated with poor adherence [21]. In contrast, Chimbetete et al, 2011 found no difference in treatment failure among those who were alcohol drinkers [8]. This could be explained by the levels of drinking alcohol in that study, which had no effect on their drug adherence levels.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In another study by Adrovandi et al, 2014, alcohol use was associated with poor adherence [21]. In contrast, Chimbetete et al, 2011 found no difference in treatment failure among those who were alcohol drinkers [8]. This could be explained by the levels of drinking alcohol in that study, which had no effect on their drug adherence levels.…”
Section: Discussionmentioning
confidence: 81%
“…This shows delay in ART initiation among adolescents. Chimbetete et al, 2011 also found that patients initiated on ART after developing AIDS related illness (WHO stage 3 & 4), and those who had low baseline CD4 counts had higher risk of treatment failure as compared to those in WHO stage 1 or 2 and those with high CD4 [8]. However the 2015 WHO guidelines expanded ART initiation to treat all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, ageing, being male, and CD4 counts <200 cells/μL were significantly associated with diabetes by one or both tests. Ageing is well documented as a risk factor for diabetes, and male sex has been reported as a risk factor for diabetes among HIV-infected patients [40], although there is no clear explanation for this. In contrast to other studies showing increased diabetes risk with increased fat, especially central fat, we found virtually no associations of BMI, FMI, FFMI or waist circumference with diabetes risk.…”
Section: Plos Onementioning
confidence: 99%
“…this phenomenon is the increased prevalence and early onset of non-infectious co-morbitidies (particularly cardiovascular disease, chronic kidney disease, type 2 diabetes mellitus, and cancer) in HIV-positive individuals [3][4][5][6]. At the same time, we are observing accentuated aging in HIV-positive people, which is associated mainly with increased immune activation, impaired regulatory functions, as well as direct effects of HIV replication in tissues and organs.…”
mentioning
confidence: 94%